Welfare state policies and far right party support: moderating 'insecurity effects' among different social groups. Issue 1 (2nd January 2022) - Vlandas, Tim; Halikiopoulou, Daphne
Abstract: This article examines the interplay between social risks, welfare state policies and far right voting. Distinguishing between compensatory and protective policies and using data from seven waves of the European Social Survey (ESS) and social policy datasets, the article tests a range of hypotheses about the extent to which welfare state policies moderate the insecurities that drive particular social groups to vote for the far right. Empirical findings confirm theoretical expectations that several welfare state policies reduce the likelihood of supporting the far right among individuals exposed to high risks including the unemployed, pensioners, low-income workers, employees on temporary contracts, individuals in large families, and individuals who are disabled/permanently sick. These findings suggest that in order to understand why some individuals vote for the far right, one should not only focus on their risk-driven grievances, but also on policies that may moderate these risks.